Fisher-Evans syndrome. Casereport in physician’s practice - A. A. Yakushev; I. G. Fedorov; L. Yu. Ilchenko; S. S. Shmycova; N. V. Ilin; G. G. Totolyan; I. O. Sirenova; I. G. Nikitin (Архивъ внутренней медицины, 2020)
The article presents the clinical features and treatment options for autoimmune thrombocytopenic purpura associated with autoimmune hemolytic anemia in the context of Fisher-Evans syndrome. Patient P. was admitted to the emergency department by an ambulance team with a direct diagnosis of acute pancreatitis. Leading clinical syndromes were hemorrhagic and anemic syndromes. A physical examination also revealed a strip-formed hemorrhagic rash in the area of inguinal folds, the anterior surface of the thighs and lower legs. During the differential diagnostic search, the diagnosis of Fisher-Evans syndrome was established. Initial oral and pulse therapy with prednisone was not effective. The patient received platelet transfusions regularly. When eltrombopag was included in therapy, there was an improvement in the patient’s condition, as well as a tendency to increase the level of platelets. On the 35th day, the patient was discharged from the hospital.We examined various clinical variants of thrombocytopenia, I meet in real clinical practice.